Cytotoxic Effect of Brazilin on DU145 Prostate Cancer Cells Using the WST-8 Assay - Alaydrus, Syafika; Niluh Puspita Dewi; Pratiwi, Dinda (Tropical Biopharmaca Research Center, IPB University, 2026)
Prostate cancer is characterized by abnormal growth of prostate gland cells due to uncontrolled cellular proliferation. Brazilin, a homoisoflavonoid compound derived from Caesalpinia sappan L., is known for its anticancer activity. This study aimed to evaluate the cytotoxic effect of brazilin on DU145 prostate cancer cells through an in vitro assay employing the WST-8 method. The results showed that both brazilin and cisplatin significantly reduced the cancer cell survival rate compared to the negative control group (p < 0.05). Although no significant difference was observed between the two compounds at the highest concentration (ns), their IC₅₀ values differed significantly (p < 0.05), recorded at 18.92 ppm for brazilin and 0.03569 ppm for cisplatin; both were classified as highly active. These findings suggest that brazilin possesses cytotoxic potential comparable to cisplatin at elevated concentrations and may be developed further as a naturally derived anticancer agent.